Pädagogisches Wissen im LehrerInnenberuf Rekonstruktive Befunde aus der schulischen Praxis - Ann-Kathrin, Dittrich (Verlag Julius Klinkhardt, 2020)
The actions of teachers in everyday school life and the associated understanding of professiona-lisation is a central topic in teacher education (Thenorth 2006; Guerriero 2017). Professional knowledge is therefore regarded as a key competence of successful teaching (Shulman 1987; Blömeke et al. 2008; Voss et al. 2015; European Commission 2018). As a result of fundamental processes of change in our society, set against the backdrop of globalisation, multiculturalism and technolog y, which are all mirrored in the school system, the professional understanding of teachers, especially the increasing importance of pedagogical knowledge, (Shulman 1987) plays a vital role in the mediation of core qualifications. The focus of this paper is the reconstruction of general pedagogical knowledge of teachers from everyday school practice. In the course of a qualitative-reconstructive study, general pedagogical knowledge of teachers is made visible with the help of interviews and lesson observations and conceptual insights gained for teacher education. Furthermore, the study presents deviations and accordances of cognitive concepts of the teachers and their acting. Another focus is on a meta-reflective development of professional knowledge and action of teachers, taking into account action-theoretical approaches.